Современное состояние популяции бобров (Castor fiber L.) верхнего и среднего течения реки Уборть и перспективы ее хозяйственного использования - Панов, Г.М. (Вестник зоологии, 1971)
The quantity of Castor jiber L. in the upper and middle flow of the river Ubort increased owing to the growth of live-stock of some beaver families that inhibited the river and migration of animals from the lower flow of the river. At present on the river Ubort from the vil. Emilchino in the south to the boundary with the Byelorussian SSR in the north all the territory is populated with the valuable rodent. In autumn 1969 there were only 220—230 beavers. The further growth in their number is inhibited by the weak forage reserve and negative effect of cattle pasture in all littoral zone. It is expedient to withdraw part of beaver life stock (50—60 individuals) for separation or for skin.